2002
DOI: 10.1116/1.1450581
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional pulsed-plasma simulation of a chlorine discharge

Abstract: A two-dimensional (r,z) continuum model was developed to study the spatiotemporal dynamics of a pulsed power (square-wave modulated) chlorine discharge sustained in an inductively coupled plasma (ICP) reactor with a planar coil. The self-consistent model included Maxwell’s equations for the power deposition profiles coupled to the electron energy equation and the species mass balances. Simulation results showed separation of the plasma into an electronegative core and an electropositive edge during the active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…The setup is connected to a diffusion chamber with identical gas pressure. Ramamurthi et al [3] showed in a similar setup that the plasma does not diffuse into this chamber for the same modulation parameters. Since the period is very small compared with the flow time-scale, we also observed that a mass flow rate of 30 sccm and 0 sccm does not change the calculations.…”
Section: Experimental Comparisonmentioning
confidence: 95%
“…The setup is connected to a diffusion chamber with identical gas pressure. Ramamurthi et al [3] showed in a similar setup that the plasma does not diffuse into this chamber for the same modulation parameters. Since the period is very small compared with the flow time-scale, we also observed that a mass flow rate of 30 sccm and 0 sccm does not change the calculations.…”
Section: Experimental Comparisonmentioning
confidence: 95%
“…Only the major ion Cl + 2 density is shown (Cl + is not included). From [76] wall sheath which contains only positive ions and electrons. For high enough negative-ion densities, the electropositive periphery is squeezed, and eventually the negative ions reach the sheath edge.…”
Section: Time Evolution Of Pulsed Electronegative Plasmas (Figures 5-7)mentioning
confidence: 99%
“…The ambipolar diffusion approximation of the ions and electron are assumed, [35,37,38] which the electrostatic field can be written as…”
Section: Transport Equations For Charged Speciesmentioning
confidence: 99%
“…Instead, we have assumed ambipolar transport in the bulk (because of very thin sheath) and replaced the sheath effect by Bohm velocity in the modeling like the other researchers in the field. [35,37,38] All the discretized equations were solved semi-implicitly (with most updated information) and sequentially at each time step. In this study, a multi-scale time-marching approach is adopted to reduce the computational cost.…”
Section: S12p-f(s) ! Etching Of P Ion-enhanced Etching Of Polymer By mentioning
confidence: 99%